Un coming-of-age métis à la française ?Lecture intersectionnelle de récits diasporiques en mouvement dans 35 Rhums (Claire Denis, 2008) et Khamsa (Karim Dridi, 2008) - Léonard Cortana; Leïla Tazir (Mise au Point)
Many French coming-of-age films have featured mixed-race youths in their transition toward adulthood since the beginning of 2000. In the anglophone world, they are called coming-of-age processes or coming-of-age films, while in France, they have no linguistic counterpart. Claire Denis' 35 shots of Rum and Karim Dridi's Kahmza came out in 2008 after the election of President Nicolas Sarkozy. The analysis of both films reveals similar tropes in expressing intergenerational traumas, rites of passage in sites of memory, and uprooting processes that often end up with exiles. Using the intersectional framework leads to an analysis of the character's construction beyond the identities of race or ethnic origins to include gender, class, and body abilities. The films become laboratories of multi-identities in construction which make the stereotypical representation of inner-city youths more complex in the French public sphere.